Mutation spectrum of Kallmann syndrome: identification of five novel mutations across ANOS1 and FGFR1 - Guoming Chu; Pingping Li; Qian Zhao; Rong He; Yanyan Zhao (Reproductive Biology and Endocrinology, 2023)
Abstract Background Kallmann syndrome (KS) is a common type of idiopathic hypogonadotropic hypogonadism. To date, more than 30 genes including ANOS1 and FGFR1 have been identified in different genetic models of KS without affirmatory genotype–phenotype correlation, and novel mutations have been found. Methods A total of 35 unrelated patients with clinical features of disorder of sex development were recruited. Custom-panel sequencing or whole-exome sequencing was performed to detect the pathogenic mutations. Sanger sequencing was performed to verify single-nucleotide variants. Copy number variation-sequencing (CNV-seq) was performed to determine CNVs. The pathogenicity of the identified variant was predicted in silico. mRNA transcript analysis and minigene reporter assay were performed to test the effect of the mutation on splicing. Results ANOS1 gene c.709 T > A and c.711 G > T were evaluated as pathogenic by several commonly used software, and c.1063-2 A > T was verified by transcriptional splicing assay. The c.1063-2 A > T mutation activated a cryptic splice acceptor site downstream of the original splice acceptor site and resulted in an aberrant splicing of the 24-basepair at the 5′ end of exon 8, yielding a new transcript with c.1063–1086 deletion. FRFR1 gene c.1835delA was assessed as pathogenic according to the ACMG guideline. The CNV of del(8)(p12p11.22)chr8:g.36140000_38460000del was judged as pathogenic according to the ACMG & ClinGen technical standards. Conclusions Herein, we identified three novel ANOS1 mutations and two novel FGFR1 variations in Chinese KS families. In silico prediction and functional experiment evaluated the pathogenesis of ANOS1 mutations. FRFR1 c.1835delA mutation and del(8)(p12p11.22)chr8:g.36140000_38460000del were assessed as pathogenic variations. Therefore, our study expands the spectrum of mutations associated with KS and provides diagnostic evidence for patients who carry the same mutation in the future.